2019
DOI: 10.1016/j.chemosphere.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential exposure to organophosphate flame retardants in mother-child pairs

Abstract: Background: Humans are ubiquitously exposed to flame retardants, including organophosphate esters (OPEs), through direct contact with consumer products or exposure through household dust.Children are at increased risk because of their proximity to dust, hand-to-mouth activity, and the importance of childhood as a critical period in neurodevelopment.Objectives: To quantify differences in exposure levels between mothers and children (three to six years of age), we analyzed urinary metabolites of OPEs. We additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 47 publications
(67 reference statements)
1
35
1
Order By: Relevance
“…We used data from these wristbands to learn about chemical exposures in this population, including common chemical exposures, relations between chemical exposures, predictors of chemical exposures, and common chemical exposure profiles. Our findings suggest that these silicone wristbands can be successfully deployed within sensitive populations to assess multipollutant exposures, extending the potential uses of this technology beyond previously successful investigations ( 15 , 16 , 18 , 21 23 ).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We used data from these wristbands to learn about chemical exposures in this population, including common chemical exposures, relations between chemical exposures, predictors of chemical exposures, and common chemical exposure profiles. Our findings suggest that these silicone wristbands can be successfully deployed within sensitive populations to assess multipollutant exposures, extending the potential uses of this technology beyond previously successful investigations ( 15 , 16 , 18 , 21 23 ).…”
Section: Discussionmentioning
confidence: 68%
“…However, relative to traditional biomarkers, the wristbands have the considerable advantage of enabling the assessment of multitudes of chemical pollutants in a single passive instrument. While previous studies have demonstrated promising relations between specific classes of exposures [e.g., PAHs (16), nicotine (67), organophosphate flame retardants (21,68)] assessed in wristbands and traditional biomarkers of exposure, to our knowledge, no work has yet assessed relations between the broad screen of chemicals used in our study with traditional biomarkers, and this is an important area for future research.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The high concentration of compound caused the impedance reduction as the compound acted as a medium between the electrode and probe. In order to determine the optimal concentration of OPFRs on the membrane, impedance values of eleven OPFRs were measured with three concentration gradients (0.3 nM, 1.5 nM and 3.0 nM) (Table S3) (Gibson et al, 2019). Cluster analysis of different concentration was revealed by a heatmap.…”
Section: Identifying Test Concentrations Of Opfrsmentioning
confidence: 99%
“…Silicone wristbands have become a popular noninvasive technique for assessing personal exposure to environmental organic contaminants in children 1–6 and adults 7–28 . The wristband samplers are generally worn for a 7‐day period to capture a wide range of chemicals that represent typical environmental exposures.…”
Section: Introductionmentioning
confidence: 99%